Beyond somatotype categories: composition-based clustering of body types in young adults - Campa, Francesco; Moon, Jordan; Petri, Cristian; Spataro, Fabrizio; Baroncini, Giulia; Faraone, Eleonora; Ortenzi, Leonardo; Bongiovanni, Tindaro; Serafini, Sofia; Izzicupo, Pascal (Frontiers in Physiology, 2025)
Background and aimsSomatotype analysis classifies individuals into 13 categories based on unique combinations of the three principal components: endomorphy, mesomorphy, and ectomorphy. This study aimed to examine sex-related differences and intra-category variability within somatotype classifications, and to characterize body composition patterns in the general population.MethodsAnthropometric data were collected from 185 males and 156 females aged 18–40 years to estimate somatotype, fat mass index (FMI), and skeletal muscle index (SMI). Sex differences were evaluated with Hotelling’s T2 and chi-square tests, while within-category morphological dispersion was quantified as Euclidean distances from centroids. K-means clustering on FMI and SMI identified Low, Medium, and High groups, and somatotype distributions across clusters were compared using chi-square and binomial tests.ResultsMen exhibited an Endomorphic-Mesomorph somatotype, whereas women displayed an Mesomorph-Endomorph profile. Hotelling’s T2 test confirmed significant sex differences in somatotype centroids (p < 0.001), and chi-square analyses showed strong associations between sex and somatotype categories (p < 0.001). Within-category morphological dispersion was significant in most groups, with males showing greater overall variability than females (p = 0.004). K-means clustering of FMI and SMI identified Low, Medium, and High groups, with somatotype distributions differing significantly across clusters (p < 0.001); a clear predominance of a single somatotype category was observed in the Medium FMI cluster of males (Endomorphic-Mesomorph, 76.8%, p < 0.001) and in the High SMI cluster of males (Endomorphic-Mesomorph, 67.5%, p = 0.019).ConclusionThese findings highlight pronounced sex-related differences, considerable intra-category variability, and distinct body composition patterns across somatotypes in the general population. Notably, although individuals classified within the same somatotype can still present heterogeneous body shapes, the Endomorphic–Mesomorph profile distinctly characterizes males with moderate fat mass and higher muscle mass.